Building menstrual health and hygiene-supportive environments: exploring teachers’ experience in rural Western Kenya - Shenkman, Julia L.; Neubauer, Leah C.; Mason, Linda; Oruko, Kelvin; Alexander, Kelly; Phillips-Howard, Penelope A.; Nyothach, Elizabeth (Frontiers in Public Health, 2023)
Introduction Existing school environments and staff play a critical role in Menstrual Health and Hygiene (MHH) for school aged girls in middle and low-income countries. This paper leverages teachers’ perspectives on menstruation and the impact of the Menstrual Solutions (MS) study, an open cluster randomized controlled feasibility study to determine the impact of puberty education, nurses support, and menstrual product provision on girls’ academic performance and emotional well-being. Methods Seventeen focus group discussions were conducted from October 2012 through November 2013 with teachers at six participating schools, held at three different time points during the study period. Results Key themes that emerged were emotions and blood, absenteeism, the role of teachers in MHH, and the impact of sensitization. Teachers noted that poor MHH had an impact on school attendance, transparency and openness with teachers, and student behavior in class. It was reported that adolescent girls would absent themselves for 3–5 days during their menstrual cycle depending on what materials they could use, and they would often shy away from teachers, when possible, only speaking to them about their menses if it was urgent or they needed to go home. Emotions such as fear and embarrassment were commonly associated with bleeding. At the midpoint and end of the study, teachers noted that the puberty education and menstrual product provision (where applicable) had a positive impact on girls’ attendance, attention, and comfort in the classroom. Girls became more open with both male and female teachers about their menses, and more comfortable and confident in the classroom among all classmates. Discussion This research highlights the importance of building an MHH-supportive environment with multiple school personnel within schools to develop a gender-equitable environment for girls to learn confidently without undue interference. Teachers are key adults in adolescent girls’ lives, having the potential to foster an environment that empowers girls with greater autonomy to manage their menses. This highlights a need to consider their perspectives in intervention development. Sensitization of teachers and puberty education across both genders are key components to developing the MHH-supportive environment in schools.